Thermal Intravesical Chemotherapy Reduce Recurrence Rate for Non-muscle Invasive Bladder Cancer Patients: A Meta-Analysis - Liu, Kang; Zhu, Jun; Song, Yu-Xuan; Wang, Xiao; Zhou, Ke-Chong; Lu, Yi; Liu, Xiao-Qiang (Frontiers in Oncology, 2020)
Background: Non-muscle invasive bladder cancer accounts for nearly eighty percent of newly diagnosed bladder cancer cases, which often recur and progress. This meta-analysis was evaluated the adverse events and recurrence rate of thermal intravesical chemotherapy versus normal temperature intravesical chemotherapy in the treatment of non-muscle invasive bladder cancer. Methods: A systematic review and cumulative analysis of studies reporting adverse event and recurrence rate of thermal intravesical chemotherapy versus normal temperature intravesical chemotherapy was performed through a comprehensive search of Pubmed, Embase, Cochranelibrary.com, CNKI, Wanfang Med Online database and VIP database. All analyses were performed using the Revman manager 5. Result: Twelve studies (11 randomized controlled trials and 1 retrospective study) including 888 patients, 445 in the thermal intravesical chemotherapy group and 443 in the normal temperature intravesical chemotherapy group, met the eligibility criteria. Patients in the thermal intravesical chemotherapy group had a lower risk of disease recurrence than those who had normal temperature intravesical chemotherapy (24 months follow-up group: RR = 0.30, 95% CI: 0.21–0.43, P ＜ 0.00001, I2 = 0%; 36 months follow-up group: RR = 0.27, 95% CI: 0.14–0.54, P = 0.0002, I2 = 0%) while no significant difference in adverse events rate (RR=0.89，95% CI =0.53-1.52；P = 0.67，I2 =78%). Conclusions: When compared with normal temperature intravesical chemotherapy, thermal intravesical chemotherapy can reduce the recurrence rate without increasing incidence of adverse events in patients with non-muscle invasive bladder cancer.